Pengelolaan Pertambangan Minyak dan Gas Bumi di Wilayah Lepas Pantai (Aceh) dalam Konteks Otonomi Daerah - Risa Shoffia (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The mandate of Article 33 of the 1945 NRI Constitution states that the natural wealth contained therein must be managed sustainably for the greatest prosperity of the Indonesian people. It is important to understand that regional autonomy originates from the management of maritime areas, which is the result of the exercise of authority relating to various activities on land. One way to improve people's welfare is by utilizing natural land and sea resources, finance and public services. One of Indonesia's greatest natural riches is natural oil and gas resources (SDA MIGAS). Normative juridical research which aims to study authority, especially the management of OIL and Gas mines in offshore areas under Aceh's special autonomy. This research is based on the diversity of legal science, which results in a normative research approach. Research shows that the law limits BPMA from managing OIL and Gas in Aceh. It is interesting to note that Aceh's OIL and GAS mines, which have large deposits, are located between 12 and 200 nautical miles. One example is the oil and gas location in Simeulue, which is located 20.5 nautical miles. Therefore, BPMA does not have the authority to negotiate, especially in terms of ratifying and signing Cooperation Contract (KKS) agreements. Therefore, laws made by the governor with the approval of the DPRA or DPRK automatically do not apply and become mere rules without action.